Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2011
DOI: 10.1145/1978942.1979287
|View full text |Cite
|
Sign up to set email alerts
|

Target assistance for subtly balancing competitive play

Abstract: In games where skills such as targeting are critical to winning, it is difficult for players with different skill levels to have a competitive and engaging experience. Although several mechanisms for accommodating different skill levels have been proposed, traditional approaches can be too obvious and can change the nature of the game. For games involving aiming, we propose the use of target assistance techniques (such as area cursors, target gravity, and sticky targets) to accommodate skill imbalances. We com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 25 publications
0
52
0
Order By: Relevance
“…Strategies for multiplayer game balancing summarized by Bateman et al include asymmetric roles, matchmaking, and individual difficulty adjustment [2]. The authors examined aim assist techniques to balance shooting-gallery games played in a co-located setting using the Nintendo Wii Remote [2].…”
Section: Balancing Multiplayer Experiencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Strategies for multiplayer game balancing summarized by Bateman et al include asymmetric roles, matchmaking, and individual difficulty adjustment [2]. The authors examined aim assist techniques to balance shooting-gallery games played in a co-located setting using the Nintendo Wii Remote [2].…”
Section: Balancing Multiplayer Experiencesmentioning
confidence: 99%
“…Multiplayer game balancing in exertion-based games is complicated by the need to consider both player skill and fitness. Although the game in [2] was played with a motionbased controller, the physical effort of pointing input does not compare to that required by many exergames. Different approaches for balancing exertion games have emerged in literature: The game Life is a Village [23] implements asymmetric player roles (cycling on a recumbent bike and using the Nintendo Wii Remote for gestural input), whereas Heart Burn [21] uses difference from target heart rates to balance for people with difference fitness levels.…”
Section: Balancing Multiplayer Experiencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has also examined player balancing, but only in a limited number of situations (e.g., [5,11,16,20]). For example, recent studies have shown that player balancing can be effectively applied in 2D and 3D shooting games [5,20].…”
Section: Introductionmentioning
confidence: 99%